2011
DOI: 10.1098/rsbl.2011.0478
|View full text |Cite
|
Sign up to set email alerts
|

Female choice and extra-pair paternity in a traditional human population

Abstract: Seeking out extra-pair paternity (EPP) is a viable reproductive strategy for females in many pairbonded species. Across human societies, women commonly engage in extra-marital affairs, suggesting this strategy may also be an important part of women's reproductive decision-making. Here, I show that among the Himba 17 per cent of all recorded marital births are attributed by women to EPP, and EPP is associated with significant increases in women's reproductive success. In contrast, there are no cases of EPP amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
75
1
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(82 citation statements)
references
References 19 publications
3
75
1
3
Order By: Relevance
“…Moreover, our result is in line with the finding that ovulating females are especially prone to double matings that promote sperm competition (Baker & Bellis 1990, Gallup et al 2006. We cannot, however, rule out the possibility that FMM fantasies above all reflect a general female interest for promiscuity (Gangestad & Simpson 2000, Scelza 2011. Surprisingly, Pound (2002) found that males also strongly preferred FMM fantasies to FFM fantasies.…”
Section: Discussionsupporting
confidence: 76%
“…Moreover, our result is in line with the finding that ovulating females are especially prone to double matings that promote sperm competition (Baker & Bellis 1990, Gallup et al 2006. We cannot, however, rule out the possibility that FMM fantasies above all reflect a general female interest for promiscuity (Gangestad & Simpson 2000, Scelza 2011. Surprisingly, Pound (2002) found that males also strongly preferred FMM fantasies to FFM fantasies.…”
Section: Discussionsupporting
confidence: 76%
“…Love match marriages are qualitatively different than arranged marriages, in that the couple chose to be together. Previous work has shown that mothers report children born into arranged marriages are more likely to be fathered by extra-marital affairs than those born into love matches, indicating increased fidelity in these marriages (Scelza, 2011). If women in love matches were on average more closely bonded to their partners, this might explain why they would feel more distressed by an emotional infidelity than a sexual one.…”
Section: Jealousy In Love Matchesmentioning
confidence: 90%
“…In interviews with 50 women, only 30% had ever heard of a modern method of contraception, and only 14% had ever used contraception, with none currently using. Second, the Himba profess to have very high rates of infidelity and have one of the highest reported rates of extra-pair paternity in the world (Scelza, 2011), reflecting a prevalent risk of paternity uncertainty for men. Relatedly, infidelity is normatively permitted for both men and women, representing a very different level of social acceptance than is found in typical western populations.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, EPCs are likely to be driven by a combination of male and female interests [1,8]. Interestingly, several studies have shown that benefits of EPC might also apply to humans, with extra-pair paternity (EPP) sometimes being associated with clear reproductive and material benefits, particularly in some traditional small-scale societies [9,10]. Nevertheless, female adultery is also common in Western society, typically occurring in 15-50% of all relationships [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…These studies have shown that median EPP rates are only between 1 and 3% in most Western European populations [11,21,23], although rates can be higher in low socioeconomic settings [24] and in some traditional small-scale societies, such as among Yanomami Indians [25] and the Himba [9]. Recent relatively unbiased studies carried out on bone marrow transplantation samples obtained maximum-likelihood estimates of EPP rates of only 0.94% in a German population [26] and of 0.65% in a Swiss population [27]-figures that are probably representative for most Western European populations.…”
Section: Introductionmentioning
confidence: 99%